Digital version of the CrAO archive of spectral observations of the Sun, carried out with the KG-2 coronagraph - Fursiak, Yu.A. (Advances in Astronomy and Space Physics, 2012)
With the development of computer technology a topical problem to digitize the astronomical data stored on various media, for their preservation and accessibility for further faster and more accurate processing has arisen. Creation of a digital archive of observational data obtained with the KG-2 coronagraph and stored on photographic films has been started at the Department of the Solar Physics of the Scientific Research Institute "Crimean Astrophysical Observatory". We obtained satisfactory results in comparing a part of the spectrum digitized with EPSON Expression 10000XL scanner and with the MF-2 type scanning microphotometer which was used before. This allows the scanner to be used in the future to create the archive. We also developed a special software, which speeds up the processing of scanned data, and tried to minimize and eliminate potential errors.